An O'Brien family Christmas - Woods, Sherryl (Don Mills, Ont. : Mira Books, 2011)
While celebrating the holidays in Dublin, Ireland, the O'Briens are in an uproar over matriarch Nell's rekindled romance with an old flame, while playboy Matthew O'Brien must convince Laila Riley, an older woman burned by love, to take a chance on him.
Keywords: Families -- Fiction; Man-woman relationships -- Fiction; Chesapeake Bay Region (Md. and Va.) -- Fiction; Dublin (Ireland) -- Fiction; Domestic fiction; Love stories; Christmas stories